An Evaluation of Web Based Expert System as a Catalyst for Maize Production in Kenya - Kipkebut, Andrew (Kabarak University, 2014)
Maize is the most important and staple food in Kenya. The Kenya Maize varieties comprise of white semi-dent grains and have been bred and selected for a wide range of climatic conditions and altitudes above sea level. The Worldwide web has played a major role in the field of expert systems. A web technology allows the knowledge engineers and domain experts to build expert systems that will have dynamic knowledge base capabilities [Marwaha et al. 2002]. With the use of the internet Domain Experts can update the knowledge at a centralized location (Server) and the users can access this knowledge on Web user Interface (Client). The use of expert system as tool in agriculture sector in Kenya has not taken off. Expert systems use knowledge to solve problems that normally would require human intelligence. Expert system has a lot of benefits especially to farmers, farming officers and Agricultural institutions. In this paper the Information was gathered through questionnaire administration in selected areas of small and large scale farmers. The questionnaires were presented in such a way that it will provide the degree of usage of the web based expert system in maize production. The validation of the results were carried out using paired- t .This paper further shows the underutilization of web based expert systems in agricultural sector in kenya and Proactive methods should be devised to improve Maize production using expert systems, which will in turn improve productivity hence increase income to the farmer, reduce losses due to, poor choice of variety, diseases prevention and pests control
Keywords: expert systems; Inference engine; Knowledge Base, Domain expert; MySQL; Web